The relationship between isokinetic knee flexion and extension muscle strength, jump performance, dynamic balance and injury risk in female volleyball players - Soylu, Ç.; Altundag, E.; Akarçesme, C.; Yildirim, N. Ü. (Journal of Human Sport & Exercise, 2020)
The relationship between balance, knee muscle strength, jump height and risk of injury has not been clearly stated in female volleyball athletes. The study was to determine whether a correlation exists between knee joint isokinetic muscle strength, risk of injury, balance and jump height in female volleyball athletes. Twenty-two female volleyball athletes were involved into the study. Knee muscle strength were evaluated with the Biodex 3® isokinetic dynamometer. Jump performances were evaluated with the countermovement (CMJ) jump test using the Vert Jump® Motion Sensitive Sensor. The injury risk for all players were evaluated by the Functional Movement Screen (FMS®). Balance measurements were performed with a dynamometer Biodex Systems 3® device. There was a significant relationship between CMJ height, knee flexion and extension peak torque and H:Q ratio values at two angular velocities, dynamic balance and total FMS® scores (p < .05). However, contralateral deficit statistically significant were not related between CMJ height, dynamic balance and FMS® scores (p > .05). We suggest that all clinicians and coaches involved in the protective and preventive rehabilitation phase evaluate these parameters and plan their training programs in line with the results obtained in increasing both individual and team performance of athletes.